Research on the Cultivation Mode of Management Accounting Talents in Applied Undergraduate Colleges in the Age of Digital Intelligence — Taking Guangzhou Huashang College as an Example - Shengying Shi; Guifen Ma (Journal of World Economy, 2024)
The in-depth application of modern information technology in the accounting industry, such as big data and artificial intelligence, has brought profound changes to the accounting industry, and the enterprises have put forward new requirements for the professional competence of accounting talents, which also poses challenges to the cultivation of undergraduate accounting talents. The paper first analyzes the demand for the professional competence of accounting talents by enterprises in the era of digital intelligence, as well as the dilemmas faced by applied undergraduate colleges and universities in the cultivation of talents. Combined with the Framework of China’s Professional Competence in Management Accounting and the competency model of management accountants, Guangzhou Huashang College actively explores the path of talent cultivation, and puts forward the creative “Three Constructions and Four Combinations”. It provides an exploratory path for undergraduate colleges and universities to cultivate accounting talents in the era of digital intelligence from the aspects of target orientation, curriculum system, practical teaching, and faculty.